2016
DOI: 10.1371/journal.pone.0157121
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Instruction on the Frequency and Characteristics of Involuntary Autobiographical Memories

Abstract: The present study investigated the effects of experimental instruction on the retrieval of involuntary autobiographical memories (IAMs). In previous studies of IAMs, participants were either instructed to record only memories (henceforth, the restricted group) or any thoughts (henceforth, the unrestricted group). However, it is unknown whether these two different types of instructions influence the retrieval of IAMs. The most recent study by Vannucci and her colleagues directly addressed this question and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 41 publications
3
55
3
Order By: Relevance
“…We expected selective monitoring to increase the likelihood that memories with low accessibility were retrieved independent of intention. First, and consistent with previous studies (Barzykowski & Niedźwieńska, ; Vannucci et al ., ), selective monitoring increased the frequency of memories (main effect of monitoring), and this increase was particularly pronounced in the voluntary condition (interaction between intention and monitoring). We therefore replicated a previous finding in the literature on involuntary memories and showed that this also holds true for voluntary memories.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We expected selective monitoring to increase the likelihood that memories with low accessibility were retrieved independent of intention. First, and consistent with previous studies (Barzykowski & Niedźwieńska, ; Vannucci et al ., ), selective monitoring increased the frequency of memories (main effect of monitoring), and this increase was particularly pronounced in the voluntary condition (interaction between intention and monitoring). We therefore replicated a previous finding in the literature on involuntary memories and showed that this also holds true for voluntary memories.…”
Section: Discussionsupporting
confidence: 92%
“…First, it can be argued that participants’ retrospection in deciding whether a thought was a memory or not may be inaccurate. This also pertains to previous studies (Barzykowski & Niedźwieńska, ; Barzykowski & Staugaard, ; Vannucci et al ., ). However, participants did not report any difficulties with this judgement and made it relatively quickly.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Participants completed a modified version of the computer-based vigilance task developed by Schlagman and Kvavilashvili (2008) and already used in previous studies (Barzykowski & Niedzẃieńska, 2016;Vannucci et al, 2014;Vannucci, Pelagatti, Hanczakowski, Mazzoni, & Rossi Paccani, 2015). The task consisted of 600 trials, presented in a fixed order, each remaining on the screen for 1.5 sec.…”
Section: 2materialsmentioning
confidence: 99%